Pelatihan Pengelolaan Arsip Keluarga Bagi Masyarakat Baturetno, Bantul - Muslikhah Dwihartanti; Joko Kumoro; Anggi Annisya Yomara; Tri Okta Erfiansah; Chikita Puspa Safitri; Aulia Zam Zam Wiratna; Titik Sumarwati; Happy Widiastuti Yulianti; Muhamad Miftakhul Hasan; Retno Wulandari; Shinta Aprilia Megantari; Rina Indriyani (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2023)
This community service activity aims to provide knowledge about family archives management for the community of Baturetno Village, Banguntapan, Bantul. The methods used in this community service activity include: 1) Lecture, the lecture method was used to provide explanation to participants regarding the concepts and steps in storing family archives effectively and efficiently. 2) Question and answer and discussion, the question-and-answer method was conducted to explore problems related to the lecture material and to answer difficulties and problems often faced in managing family archives in the community. 3) Practice of family archives management, this method gave participants the opportunity to store family archives and create an effective and efficient archival system. The community service activity has been carried out well and has provided knowledge in the field of family archives management for the community. The knowledge delivered included theory and classification of family archives as well as the practice of family archives management. In addition, participants were also informed about how to maintain stored documents so they can remain durable and last longer. The community service activity was implemented successfully exceeding the predetermined target. Participant attendance reached 111.43% from the target of 80%.